[FOSS-GPS] Introduction
Marcus Wolschon
Marcus at Wolschon.biz
Mon Sep 22 03:28:54 EDT 2008
2008/9/20 Abdelrazak Younes <younes.abdel at gmail.com>:
> Here is a simple algorithm for you:
>
> Ps = P * A + Pp * B
>
> Where:
> Ps is the smoothed position
> A + B = 1, for example A = 0.01 and B = 0.99
> P is the GPS position solution
> Pp is the projected position:
> Pp(t_n) = P(t_n) + (t_n - t_{n-1}) * V(t_n)
>
> Where:
> t_n is the current epoch
> t_{n-1} is the previous epoch
> V(t_n) is the current GPS Velocity solution.
I guess that would be
Pp(t_n) = P(t_{n-1}) + (t_n - t_{n-1}) * V(t_{n-1})
as you don't want to calculate Pp(t_{n+1) but
Pp(t_n) instead.
Marcus
More information about the FOSS-GPS
mailing list